Lifestyle and well-being of university students in Japan: a cross-sectional study - Takemune Fukuie; Koshiro Inoue; Akihiko Yamaguchi (Academia Mental Health & Well-Being)
Mental health, academic motivation, and exercise participation remain critical issues for well-being of university students. This study aimed to explore lifestyle elements that influence mental health, academic motivation, and participation of three types of exercise among university students. This cross-sectional study was conducted between October 2022 and December 2022. A total of 240 first-year students (mean age: 18.70 ± 0.53 years; age range: 18–21; 166 female) participated in the study. Participants measured and recorded their lifestyle for a week using accelerometer and an Excel format. Measurements included daily step counts; dietary habits; sleep habits; exercise participation by type, such as aerobic exercise (AE), resistance exercise (RE), and flexibility exercise (FE); screen time; eye fatigue; club activities; part-time job time; depression; and academic motivation. Path analysis revealed that longer FE and higher subjective sleep quality predicted lower depression (β = −0.11, P < 0.05; β =−0.23, P < 0.001). Screen time commonly predicted depression (β = 0.11, P < 0.05) and academic motivation (β = −0.15, P < 0.05). Frequency of exercise less than 5 min commonly predicted total time of AE (β = 0.20, P < 0.01), RE (β = 0.23, P < 0.001), and FE (β = 0.21, P < 0.001). Decreasing screen time could be a common key factor for good mental health and academic motivation. Increasing short-term frequent exercise could be an implementable strategy for increasing participation in all three types of exercise.